Analisis Pengaruh Kompetensi, Komitmen dan Motivasi Terhadap Kinerja Dosen Perguruan Tinggi Swasta Kopertis Wilayah XII Maluku dan Maluku Utara Di Kota Ambon - Melda Wasahua (Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2018)
The condition of the lecturers of Private Universities in the Region XII of Maluku and North Maluku who have few new academic levels. Many lecturers who have not carried out tridharma activities in full are only limited to education and teaching activities. There are still many lecturers who carry out Tri darma research and dedication only to take care of the academic level. Not yet used as a target of the performance of the lecturers themselves. Competence, commitment and motivation are the main factors that influence the performance of private university lecturers. This study aims to obtain the results of studies on competency, commitment, motivation and performance of lecturers and to reveal the analysis of the influence of competence, commitment and motivation on the performance of lecturers. The research method used is descriptive and explanatory survey with a questionnaire as a primary data collection tool. The sample size of 81 lecturers was taken through purposive random sampling technique, with lecturer information sources spread across 9 private universities in the Kopertis Region XII Maluku and North Maluku in Ambon City. Data analysis using multiple regression tests with SPSS. The results showed that competence had a significant and positive influence on the performance of the Lecturer with a score of 8.408 > table 1.665 and a significance of 0.000 < 0.05, commitment had a significant and positive influence on the performance of lecturers with t count 2.936 > t table 1.665 and significance 0.004 < 0.05. Motivation has a significant and positive effect on the performance of lecturers with t count 2.697 > t table 1.665 and the significance value of 009 < 0.05, and Competence, Commitment and motivation simultaneously have a significant effect on the performance of lecturers F 222.254 > Ftable 2.72 and significance 0.000 < 0.05 The results of this study are that there is a significant effect of competence on the performance of lecturers, then there is a significant influence on commitment to lecturer performance and there is a significant effect of motivation in improving lecturer performance and significant influence jointly on competence, commitment and motivation on lecturer performance.Keywords: Competence, Commitment, Motivation, Lecture Performance